Successful treatment of a subcutaneous axillary abscess due to Staphylococcus lentus in a rabbit - Javad Khoshnegah; Hossein Kazemi Mehrjerdi; Mehrnaz Rad (The Iranian Journal of Veterinary Science and Technology, 2009)
A 2-year-old, female, crossbred pet rabbit was found to have a subcutaneous axillary abscess from which Staphylococcus lentus was the sole isolate. The S. lentus - an indigenous bacterium in rabbit saliva - probably was introduced into the axillary region during licking of a small wound. Due to severe neutropenia, the rabbit had developed a serious infection within a few weeks. Marked clinical improvement was observed following abscess excision and treatment with sulfamethoxaszole-trimethoprim. S. lentus should be added to the growing list of bacteria causing infection especially subcutaneous abscesses in rabbits.